The relationship between diet and tooth complexity in living dentigerous saurians. (31st January 2017) - Melstrom, Keegan M.
Abstract: Living saurian reptiles exhibit a wide range of diets, from carnivores to strict herbivores. Previous research suggests that the tooth shape in some lizard clades correlates with diet, but this has not been tested using quantitative methods. I investigated the relationship between phenotypic tooth complexity and diet in living reptiles by examining the entire dentary tooth row in over 80 specimens comprising all major dentigerous saurian clades. I quantified dental complexity using orientation patch count rotated (OPCR), which discriminates diet in living and extinct mammals, where OPCR‐values increase with the proportion of dietary plant matter. OPCR was calculated from high‐resolution CT‐scans, and I standardized OPCR‐values by the total number of teeth to account for differences in tooth count across taxa. In contrast with extant mammals, there appears to be greater overlap in tooth complexity values across dietary groups because multicusped teeth characterize herbivores, omnivores, and insectivores, and because herbivorous skinks have relatively simple teeth. In particular, insectivorous lizards have dental complexities that are very similar to omnivores. Regardless, OPCR‐values for animals that consume significant amounts of plant material are higher than those of carnivores, with herbivores having the highest average dental complexity. These results suggest reptilian tooth complexity is related to diet, similar to extinct and extant mammals, although phylogenetic history also plays a measurable role in dental complexity. This has implications for extinct amniotes that display a dramatic range of tooth morphologies, many with no modern analogs, which inhibits detailed dietary reconstructions. These data demonstrate that OPCR, when combined with additional morphological data, has the potential to be used to reconstruct the diet of extinct amniotes. J. Morphol. 278:500–522, 2017. © 2017 Wiley Periodicals, Inc. Abstract : Analysis of saurian dental complexity demonstrates that carnivores, such as Varanus rudicollis (left), have simpler teeth than omnivores and herbivores ( Platysaurus guttatus and Amblyrhynchus cristatus, middle and right, respectively). Abbreviations: OPCR, orientation patch count rotated.